Designing solutions for your business problems : A structured process for managers and consultants - Vandenbosch, Betty (San Francisco Jossey-Bass, 2003)
Designing Solutions for Your Business Problems will teach you how to curtail investigation and generate and justify ideas without sacrificing thoroughness, creativity, persuasiveness, and fit. Betty Vandenbosch offers a variety of useful techniques such as the "scooping diagram," which provides a framework for action, and the "logic diagram," which tests the validity of a potential solution. In addition, the book contains illustrative real-life examples of the Designing Solutions approach from a variety of organizations.
Includes bibliographical references and indexes
Keywords: Quản trị kinh doanh